Successful Pregnancy Following ICSI Using Array Comparative Genomic Hybridization for Preimplantation Genetic Screening - Jariya Lorwatthanasirikul; Wiwat Quangkananurug; Tosaporn Ruengkris; Sujin Chanchamroen; Surachai Pornwiroon; Nana Rayasawath (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
A 41-year-old woman with 2 previous failed IVF cycles was reported. After controlled ovarian hyperstimulation and then intracytoplasmic sperm injection (ICSI) of 4 metaphase II oocytes with ejaculated sperm was performed, 4 fertilized oocytes occurred. Two blastocysts were biopsied on day 5, one of them was chromosomally normal after array Comparative Genomic Hybridization (aCGH)-based preimplantation genetic screening (PGS). The successful pregnancy was achieved after blastocyst transfer. The aCGH-based PGS may be the preferred method to select the balanced and euploid embryo before transfer in IVF.